PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK ROUND ROBIN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X SMA NEGERI 14 PEKANBARU - Diah Permata Suci; Herdini '; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research about application of cooperative learning model Round Robin technique has been done to know the improvement of student’s achievement on chemical bonds subject in class X SMAN 14 Pekanbaru. This research was experimental research with pretest-posttest design. The sample consisted of two classes, X2 class as experiment class and X1 class as control class that randomly selected after testing homogeneity. The experiment class was a class that treated by applying cooperative learning model Round Robin technique, while the control class was not. Analysis of data used t-test. Based on analysis data by using t-test formula obtained tcount>ttable (2,89 > 1,67). It means that the application of cooperative learning model Round Robin technique can improve student’s achievement on chemical bonds subject in class X SMAN 14 Pekanbaru with the coefficient of influence is 10,39%.Keywords: Cooperative Learning, Round Robin, Student Achievement, Chemical Bonds